Implementation of C4.5 Method and Artificial Neural Networks to Predict Sales - Elsa Trisna Putri (Journal of Computer Scine and Information Technology, 2021)
Technology and communication is currently growing along with the increasing needs of each individual in various fields such as: business, education, agriculture, health and technology. With the development of technology today, everyone can communicate and obtain and convey various information needed anytime and anywhere quickly, accurately and dynamically.Sales is an activity of buying and selling products or goods carried out between sellers and buyers, can interact within the same scope or online by using legal payment transactions. Building materials are materials used to design buildings such as houses, mosques, schools etc. For buildings, many natural materials are used such as: clay, sand, wood or bamboo, stone and others. In this study, the implementation of the c45 method and an artificial neural network to predict sales for the next year. The sale of building materials at the prayer shop, whose sales are not yet computerized by designing a computerized sales system. Toko Doa Mama is a building shop that sells various building materials such as: sand, paint, wood, or bamboo, saws, cement, roof tiles, gravel, nails, bricks, and others. But sales and marketing are still not computerized which results in frequent errors in calculating sales transactions, data collection of incoming goods and outgoing goods which are still in the form of archives, resulting in accumulation and lack of data security. Therefore, we need a computerized where the computer can help a job to be more effective and efficient